The impact of online learning on the mathematics learning process in Indonesia: A meta-analysis - Muhammad Turmuzi; Ulfa Lu'luilmaknun (OmniaScience, 2023)
The goal of this meta-analysis is to ascertain how online learning has affected Indonesian students' ability to learn mathematics. Descriptive analysis was used to compile info from 41 pieces of information about the research, such as sample size, standard deviation, mean values for the experimental and control groups, and other data. Data analysis methods include testing for heterogeneity, effect size calculations, summary outcome calculations the random effect models, and publication bias identification. Forest plots are used as the data source for the meta-analysis. The outcomes revealed that the impact of online learning in Indonesia was 1,268 which had a high influence on the education process of student mathematics. The online learning model also has a higher impact at the primary school level than at the middle school, high school, and university levels. The research area in Indonesia that has the biggest impact is the province of North Sumatra. A sample size of more than 30 gives a greater effect than a sample size of 1-30.